Farm typologies for understanding farm systems and improving agricultural policy - Robert Huber; Bartosz Bartkowski; Calum Brown; Nadja El Benni; Jan-Henning Feil; Pascal Grohmann; Ineke Joormann; Heidi Leonhardt; Hermine Mitter; Birgit Müller (Agricultural Systems, 2024)

Manipulation of phyllosphere bacterial communities reversibly alters the plant microbiome and leaf traits in the field - Lisa-Maria Ohler; Sarah Seeleitner; Stefan Haselberger; Sabine Kraushaar; Jan-Christoph Otto; Birgit Mitter; Robert R. Junker (Alpine Botany, 2022)
Bacterial communities in the phyllosphere are shaped by host genotype and phenotype and spatio-temporal variation of the environment. In turn, bacteria have the potential for altering the plant phenotype. Field experiments can help to estimate bacterial effects on plant functional traits under natural conditions. We used a transplantation approach of culturable bacterial communities to explore how manipulation of leaf-associated microbial communities in two different successional stages within a glacier foreland can influence microbial composition and functional plant traits. Our study documents successional stage-specific variations in the composition of foliar bacterial communities and shifts therein throughout a season and between years. We show that cultured bacteria transferred between plant communities can alter diversity and composition of the microbiome on plant community level as well as species-specific functional plant traits of two selected plant species within one growing season. Furthermore, our results demonstrate a strong resilience of plant-associated bacterial communities and of plants in response to bacterial invaders. Our study illustrates that inoculation experiments in the field with naturally occurring microbial communities of wild plants are suited to investigate complex interactions between microbial communities, the environment, and plant traits.

The plant endosphere world – bacterial life within plants - Stéphane Compant; Marine C. Cambon; Corinne Vacher; Birgit Mitter; Abdul Samad; Angela Sessitsch (Environmental Microbiology, 2021)
Summary The plant endosphere is colonized by complex microbial communities and microorganisms, which colonize the plant interior at least part of their lifetime and are termed endophytes. Their functions range from mutualism to pathogenicity. All plant organs and tissues are generally colonized by bacterial endophytes and their diversity and composition depend on the plant, the plant organ and its physiological conditions, the plant growth stage as well as on the environment. Plant‐associated microorganisms, and in particular endophytes, have lately received high attention, because of the increasing awareness of the importance of host‐associated microbiota for the functioning and performance of their host. Some endophyte functions are known from mostly lab assays, genome prediction and few metagenome analyses; however, we have limited understanding on in planta activities, particularly considering the diversity of micro‐environments and the dynamics of conditions. In our review, we present recent findings on endosphere environments, their physiological conditions and endophyte colonization. Furthermore, we discuss microbial functions, the interaction between endophytes and plants as well as methodological limitations of endophyte research. We also provide an outlook on needs of future research to improve our understanding on the role of microbiota colonizing the endosphere on plant traits and ecosystem functioning.

Editorial special issue: the soil, the seed, the microbes and the plant - Eric B. Nelson; Philippe Simoneau; Matthieu Barret; Birgit Mitter; Stéphane Compant (Plant and Soil, 2018)

Commentary: seed bacterial inhabitants and their routes of colonization - Carolina Escobar Rodríguez; Birgit Mitter; Matthieu Barret; Angela Sessitsch; Stéphane Compant (Plant and Soil, 2018)

Editorial special issue: soil, plants and endophytes - Stéphane Compant; Kari Saikkonen; Birgit Mitter; Andrea Campisano; Jesús Mercado-Blanco (Plant and Soil, 2016)

Cadmium-tolerant bacteria induce metal stress tolerance in cereals - Iftikhar Ahmad; Muhammad Javed Akhtar; Zahir Ahmad Zahir; Muhammad Naveed; Birgit Mitter; Angela Sessitsch (Environmental Science and Pollution Research, 2014)

Improved group‐specific primers based on the full SILVA 16 S r RNA gene reference database - Stefan Pfeiffer; Milica Pastar; Birgit Mitter; Kathrin Lippert; Evelyn Hackl; Paul Lojan; Andreas Oswald; Angela Sessitsch (Environmental Microbiology, 2014)
Summary Quantitative PCR ( qPCR ) and community fingerprinting methods, such as the Terminal Restriction Fragment Length Polymorphism ( T ‐ RFLP ) analysis, are well‐suited techniques for the examination of microbial community structures. The use of phylum‐ and class‐specific primers can provide enhanced sensitivity and phylogenetic resolution as compared with domain‐specific primers. To date, several phylum‐ and class‐specific primers targeting the 16 S ribosomal RNA gene have been published. However, many of these primers exhibit low discriminatory power against non‐target bacteria in PCR . In this study, we evaluated the precision of certain published primers in silico and via specific PCR . We designed new qPCR and T ‐ RFLP primer pairs (for the classes Alphaproteobacteria and Betaproteobacteria , and the phyla Bacteroidetes , Firmicutes and Actinobacteria ) by combining the sequence information from a public dataset ( SILVA SSU Ref 102 NR ) with manual primer design. We evaluated the primer pairs via PCR using isolates of the above‐mentioned groups and via screening of clone libraries from environmental soil samples and human faecal samples. As observed through theoretical and practical evaluation, the primers developed in this study showed a higher level of precision than previously published primers, thus allowing a deeper insight into microbial community dynamics.

The endophyte Enterobacter sp. FD17: a maize growth enhancer selected based on rigorous testing of plant beneficial traits and colonization characteristics - Muhammad Naveed; Birgit Mitter; Sohail Yousaf; Milica Pastar; Muhammad Afzal; Angela Sessitsch (Biology and Fertility of Soils, 2014)

Identification of a mutation in exon 27 of the RB1 gene associated with incomplete penetrance retinoblastoma - Diana Mitter; Diane Rushlow; Inga Nowak; Birgit Ansperger-Rescher; Brenda L. Gallie; Dietmar R. Lohmann (Familial Cancer, 2009)